Psychomotor Readiness of the Community Against the Early Warning System Facing Flood Disaster - Mehat, Nurul Aini; Syed Hussain, Tuan Pah Rokiah (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
The frequency of extreme flood events has left psychomotor impression on community. This situation requires researchers to explore the psychomotor aspects of community members (in terms of initial preparation and financial ability) by testing new variables based on information dissemination and community response capability. This study examined the relationship between information dissemination factors and response capability with community psychomotor readiness to face flood disaster. A survey was conducted on 343 respondents in Kemaman District in Terengganu State, Malaysia. The findings show that the more people received warning information, the more prepared for flood disaster; the fastest community's ability to respond to the flood disaster, the better initial preparation has be done in the face of the flood disaster; the sooner the dissemination of warning information is issued, the more family financial resources can be saved in the face of floods; The higher the ability of a person to react in action, the better their financial ability is related to the flood disaster. In conclusion, the study points out that, in the context of the relationship test found that initial preparations of respondents in relation to flood disasters are determined by the factors of information dissemination and financial ability, however the aspect of financial ability is dependent on both factors.